High-entropy alloy nano-particles used as biocatalyst and application of high-entropy alloy nano-particles
By preparing pH-adaptive PtFeCuCoNi high-entropy alloy nanoparticles, the problem of antibiotics killing MRSA and scavenging reactive oxygen species under different pH conditions was solved, achieving efficient sterilization and tissue repair effects.
Patent Information
- Application Number
- CN202511446528.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-10-11
AI Technical Summary
Existing antibiotics are unable to effectively kill drug-resistant strains such as MRSA under different pH conditions and control reactive oxygen species during chronic inflammation, leading to difficult-to-cure infections and delayed tissue repair.
We developed pH-adaptive PtFeCuCoNi high-entropy alloy nanoparticles, which were prepared by solvothermal synthesis. These nanoparticles possess the ability to generate reactive oxygen species for sterilization under acidic conditions and to scavenge reactive oxygen species under neutral conditions, mimicking the activities of peroxidase, superoxide dismutase, and catalase.
It achieves efficient killing of MRSA in acidic environments and scavenging of reactive oxygen species in neutral environments, reducing tissue oxidative damage and promoting wound healing, providing an antibiotic-free strategy to address the challenges of drug resistance and chronic inflammation.
Smart Images

Figure CN120919164A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalytic materials technology, specifically relating to a high-entropy alloy nanoparticle used as a biocatalyst and its applications. Background Technology
[0002] Antibiotic-resistant bacterial infections present with a wide range of clinical manifestations, particularly prevalent in chronic, non-healing skin wounds, and have become a significant global health burden. The wound microenvironment undergoes dynamic pH changes: in the acute phase, bacterial overgrowth and biofilm formation acidify the tissue by producing organic acids, hindering host defense mechanisms and reducing antibiotic efficacy. As the infection progresses to the chronic inflammatory stage, persistent M1 macrophage infiltration and the release of pro-inflammatory cytokines cause the local pH to return to neutral, while simultaneously generating excessive reactive oxygen species (ROS) that damage endothelial cells and fibroblasts, delaying the repair process. This pH-driven paradox—requiring potent bactericidal action in an acidic microenvironment followed by ROS scavenging and immune regulation under neutral pH conditions—exceeds the capabilities of existing antibiotics, especially against multidrug-resistant strains such as methicillin-resistant Staphylococcus aureus (MRSA). Therefore, there is an urgent need to develop antibiotic-free, pH-adaptive interventions that can gradually eliminate pathogens under acidic conditions, subsequently switching to antioxidant and immunomodulatory functions to accelerate tissue regeneration.
[0003] Peroxisome-mediated regulation of reactive oxygen species (ROS) is a core mechanism of innate immunity, driving oxidative cascade reactions to eliminate pathogens while minimizing collateral damage. Specifically, oxidases (OXD) and peroxidases (POD) generate ROS to disrupt bacterial membrane structures, oxidize proteins and nucleic acids, and disintegrate biofilms. After pathogens are cleared, catalase (CAT) breaks down residual H2O2 into water and oxygen, maintaining redox balance and protecting host cells. However, persistent or excessive ROS generation—especially during chronic inflammation—can breach these defense mechanisms, exacerbating inflammatory signaling and causing oxidative damage to surrounding tissues, ultimately delaying the repair process. Although peroxisome enzymes can ingeniously coordinate ROS metabolism, their direct therapeutic application is limited by short circulating half-lives, poor stability, and potential immunogenicity. Against this backdrop, engineered ROS regulation has emerged as a non-antibiotic strategy to achieve potent bactericidal activity and controlled inflammation resolution. Recent advancements in nanotechnology have spurred the development of various enzyme-mimicking materials, including inorganic nanoparticles, carbon-based nanostructures, nanoliposomes, and metal-organic frameworks, which possess both ROS generation and scavenging capabilities. However, many of these platforms still suffer from limited catalytic turnover and insufficient control over ROS release, leading to incomplete pathogen eradication or unintended oxidative damage to host tissues.
[0004] High-entropy alloys (HEAs), with their multi-element synergistic effects, provide an unprecedented platform for simulating enzyme catalysis. By combining five or more transition metals in near-equal atomic proportions (5%–35%), HEAs utilize high configurational entropy, lattice distortion, and slow diffusion to form stable single-phase solid solutions. This "cocktail effect" constructs a dense array of chemically active sites, allowing for precise control of the alloy's d-band centers and oxygen binding characteristics, resulting in catalytic performance and stability surpassing that of single-metal alloys. Therefore, HEAs have become a cornerstone in energy conversion and environmental catalysis. However, their application in biomedical reactive oxygen species (ROS) regulation is still in its early stages, limited by harsh activation conditions, limited aqueous stability, and biocompatibility issues. To bridge this gap, it is necessary to rationally design HEA nanozymes with controllable size, surface chemical properties, and pH-responsive redox behavior to achieve safe and effective regulation of ROS in vivo. Summary of the Invention
[0005] Inspired by the adaptability of natural peroxisomes, this invention develops pH-adaptive PtFeCuCoNi high-entropy alloy nanoparticles through a one-step solvothermal synthesis method. It was found that under acidic conditions, they can act as potent oxidases, generating reactive oxygen species (ROS) to effectively kill bacteria such as MRSA. Under neutral conditions, they can function as superoxide dismutase and catalase-like enzymes, efficiently scavenging intracellular ROS, alleviating oxidative stress, and exerting cytoprotective effects.
[0006] Specifically, in one aspect, the present invention provides a high-entropy alloy nanoparticle, the composition of which includes Pt, Fe, Cu, Co and Ni.
[0007] Furthermore, the atomic proportions of Pt, Fe, Cu, Co, and Ni in the high-entropy alloy nanoparticles are each 5% to 35%.
[0008] Furthermore, the atomic ratio of Pt, Fe, Cu, Co and Ni in the high-entropy alloy nanoparticles is 19.1:14.7:20.9:22.3:23.0.
[0009] Furthermore, the high-entropy alloy nanoparticles have a single-phase solid solution structure.
[0010] Furthermore, the high-entropy alloy nanoparticles possess the ability to promote the generation and removal of reactive oxygen species in a pH-adaptive manner.
[0011] Furthermore, the high-entropy alloy nanoparticles possess pH-adaptive POD-like, SOD-like, and / or CAT-like enzyme activities.
[0012] As used herein, pH adaptability means that the high-entropy alloy nanoparticles exhibit different properties at different pH levels, such as the ability to promote the generation or scavenging of reactive oxygen species, or different enzyme catalytic activities.
[0013] Furthermore, the high-entropy alloy nanoparticles have the ability to promote the generation of reactive oxygen species under acidic conditions and the ability to promote the scavenging of reactive oxygen species under neutral conditions.
[0014] Furthermore, the high-entropy alloy nanoparticles exhibit POD-like enzyme activity under acidic conditions and SOD-like and / or CAT-like enzyme activity under neutral conditions.
[0015] The high-entropy alloy nanoparticles described herein can be prepared using methods known in the art for preparing high-entropy alloy materials.
[0016] As an example, the present invention provides a method for preparing high-entropy alloy nanoparticles as described herein, comprising the following steps: performing a solvothermal reaction of Pt salt, Fe salt, Cu salt, Co salt and Ni salt in a solvent to obtain high-entropy alloy nanoparticles.
[0017] Furthermore, as used herein, the salt of a metal is at least one of a metal acetate, acetylacetone salt, chloride salt, nitrate, and their hydrates.
[0018] Further, the solvent is one or a mixture of several of N,N-dimethylformamide (DMF), ethylene glycol (EG), methanol, ethanol and acetone.
[0019] Preferably, the solvent is a mixture of DMF and EG.
[0020] Furthermore, the solvothermal reaction includes reacting at 150-240°C for 1-10 hours.
[0021] Furthermore, the preparation method includes dissolving Ga salt, Pd salt, Ru salt, Ir salt and Mn salt in a solvent, ultrasonically mixing, carrying out a solvothermal reaction, collecting the product by centrifugation, washing and drying to obtain PtFeCuCoNi high-entropy alloy nanoparticles.
[0022] In another aspect, the present invention provides the application of high-entropy alloy nanoparticles as described herein as biocatalysts.
[0023] Furthermore, the application is not intended for diagnosis or treatment.
[0024] Furthermore, the biocatalyst has the ability to promote the generation and removal of reactive oxygen species in a pH-adaptive manner.
[0025] Furthermore, the biocatalyst has pH-adaptive POD-like, SOD-like, and / or CAT-like enzyme activities.
[0026] Furthermore, the biocatalyst has the ability to promote the generation of reactive oxygen species under acidic conditions and the ability to promote the scavenging of reactive oxygen species under neutral conditions.
[0027] Furthermore, the biocatalyst exhibits POD-like enzyme activity under acidic conditions and SOD-like and / or CAT-like enzyme activity under neutral conditions.
[0028] In other respects, the present invention provides the use of high-entropy alloy nanoparticles as described herein in the preparation of materials for scavenging bacteria and disrupting biofilms under acidic conditions and / or scavenging reactive oxygen species under neutral conditions, protecting cells to alleviate damage caused by oxidative stress, and anti-inflammatory effects.
[0029] Furthermore, the bacteria are drug-resistant.
[0030] Furthermore, the bacteria include, but are not limited to, drug-resistant Staphylococcus aureus.
[0031] Furthermore, the bacteria include, but are not limited to, methicillin-resistant Staphylococcus aureus.
[0032] Furthermore, the minimum inhibitory concentration of the high-entropy alloy nanoparticles is 8 μg / mL.
[0033] In other respects, the present invention also provides the use of high-entropy alloy nanoparticles as described herein in the preparation of products for treating wound infections and accelerating wound healing.
[0034] Furthermore, the wound infection includes bacterial infection.
[0035] Furthermore, the bacteria are drug-resistant.
[0036] Furthermore, the bacteria include, but are not limited to, drug-resistant Staphylococcus aureus.
[0037] Furthermore, the bacteria include, but are not limited to, methicillin-resistant Staphylococcus aureus.
[0038] Beneficial effects of the present invention
[0039] The PtFeCuCoNi high-entropy alloy nanoparticles of this invention are composed of five transition metals with similar atomic radii, achieving both a more ideal antibacterial effect and reducing the amount of precious metals used. The strong interactions between the d electrons of each element in the nanoparticles optimize the electron distribution around the bulk material's electric field, thereby enhancing the adsorption and desorption capacity of intermediate products at the surface active sites and significantly improving the performance of the nanocatalyst. When exposed to the acidic environment of infected tissue, its oxidase and peroxidase-like functions release a burst of ROS, effectively killing bacteria such as MRSA and disrupting biofilms. As the local pH returns to physiological levels during the healing process, the superoxide dismutase and catalase-like functions efficiently remove excess ROS, alleviating oxidative stress. Theoretical modeling and experimental verification both confirm its superior catalytic performance: the peroxidase-like titer is 10.23 μM s⁻¹, and the catalase-like titer reaches 74.69 μM s⁻¹, surpassing mainstream nanozyme products, achieving ultra-low-dose, highly efficient sterilization with extremely low cytotoxicity. Crucially, these high-entropy alloy nanoparticles can also regulate macrophage polarization in stages—first enhancing M1-mediated bacterial clearance, and then inducing M2-driven regenerative repair responses. Comprehensive in vitro and in vivo studies have confirmed that this technology can rapidly clear bacteria, efficiently eliminate reactive oxygen species (ROS), and protect endothelial cells, fibroblasts, and macrophages, ultimately significantly accelerating wound healing. This pH-adaptive HEA nanozyme platform provides a time-programmable, antibiotic-free strategy that overcomes drug resistance and chronic inflammation while promoting tissue regeneration. Attached Figure Description
[0040] Figure 1 The synthesis and characterization of PtFeCuCoNi high-entropy alloy nanoparticles are shown. (a) Schematic diagram of the synthesis and structure of PtFeCuCoNi high-entropy alloy (NPs) nanoparticles. (b) Scanning electron microscope (SEM) images of platinum nanoparticles and (c) PtFeCuCoNi high-entropy alloy nanoparticles. (d) Transmission electron microscope (TEM) image of PtFeCuCoNi high-entropy alloy nanoparticles. (e) High-resolution TEM image of PtFeCuCoNi high-entropy alloy nanoparticles, and the corresponding Fast Fourier Transform (FFT) spectra within the dashed boxes (e1, e2). (f) Inverse Fast Fourier Transform (FTT) spectra corresponding to e1 and e2. (g) High-angle angular momentum scattering (HAADF)-STEM-EDS elemental distribution map of PtFeCuCoNi high-entropy alloy nanoparticles.
[0041] Figure 2The structural characterization of PtFeCuCoNi high-entropy alloy nanoparticles is shown. (a) X-ray diffraction patterns of PtFeCuCoNi high-entropy alloy nanoparticles and their comparison with standard PDF cards. (b) STEM-EDS energy dispersive spectroscopy of PtFeCuCoNi high-entropy alloy nanoparticles (inset shows the corresponding ICP-OES detection results). XPS spectra of Pt 4f (c), Fe 2p (d), Copper 2p (e), Cobalt 2p (f), and Nickel 2p (g) of PtFeCuCoNi high-entropy alloy nanoparticles. (h) Pt L3-edge XANES spectra of PtFeCuCoNi high-entropy alloy nanoparticles and reference samples (PtO2 and platinum foil). (i) Fourier transform k2-weighted EXAFS spectra. (j) In-situ probe spectral analysis of different samples at the Pt L3 edge.
[0042] Figure 3 This study presents the pH-tunable ROS catalytic activity of platinum-iron-copper-cobalt-nickel high-entropy alloy nanoparticles (PtFeCuCoNi HEA NPs). (a) Schematic diagram of ROS generation activity of PtFeCuCoNi HEA NPs in an acidic environment, and comparison of scavenging activity in a neutral environment. (b) Quantitative analysis and UV-Vis spectral data of peroxidase-like activities of platinum nanoparticles and PtFeCuCoNi HEA NPs. Data are expressed as mean ± standard deviation, n = 3 independent experiments. (c) PtFeCuCoNi nanoparticles exhibit pH-adaptive POD simulation activity (n = 3 independent experiments, data are expressed as mean ± SD). au represents arbitrary units. (d) TMB-based UV-Vis spectroscopy simulates POD activity in the presence of quaternary alloy nanoparticles and PtFeCuCoNi nanoparticles.
[0043] Figure 4 This study demonstrates the pH-dependent ROS generation and scavenging activity of PtFeCuCoNi high-entropy alloy nanoparticles (HEA NPs). (a) Michaelis-Menten kinetics of peroxidase-like activity of platinum nanoparticles and PtFeCuCoNi HEA NPs with hydrogen peroxide as a substrate. (b) Comparative analysis of TON and Vmax values with previously reported advanced peroxidase-like catalysts. (c) In the catalytic oxidation of trimethylbromine (TMB) using the PtFeCuCoNi HEA NP system, tert-butanol (TBA) quenches •OH radicals, benzoquinone (BQ) quenches O2- radicals, and singlet oxygen is quenched by hydroxyl radicals (sodium azide). 1 Experimental results for O2). Data are expressed as mean ± standard deviation, n = 3 independent experiments. (d) EPR spectra were used to record •O2- and 1O2 signal. (e) SOD-like activity of Pt nanoparticles and PtFeCuCoNi high-entropy alloy nanoparticles (n = 3 independent experiments, data are presented as mean ± standard deviation). (f) CAT-like performance changes over time in the presence of biocatalyst and hydrogen peroxide, determined by the TiSO4 method. (g) Oxygen production concentration measured using a dissolved oxygen analyzer containing biocatalyst and hydrogen peroxide. (h) Statistical analysis of oxygen production kinetic parameters of Pt nanoparticles and PtFeCuCoNi high-entropy alloy nanoparticles. (i) Comparative analysis of TON and Vmax values with those of previously reported advanced CAT catalysts.
[0044] Figure 5 The in vitro bactericidal effect of PtFeCuCoNi high-entropy alloy nanoparticles on methicillin-resistant Staphylococcus aureus (MRSA) was evaluated. (a) Survival rates of MRSA captured in different concentrations of platinum and platinum-iron-copper-cobalt-nickel alloy media (n = 3 independent replicates). (b) Bacterial viability of MRSA after treatment with H2O2 (0.2 mM), PtFeCuCoNi at concentrations of 0, 2, 4, 6, 8, 16, 32, 64, 96, and 128 μg·mL⁻¹. PtFeCuCoNi and H2O2 (0.2 mM) were reacted with 1 mL of bacterial suspension (10 μg·mL⁻¹). 6 The culture suspension was incubated at 37°C for 12 h with CFU·mL⁻¹. The culture suspension was then diluted 10⁻⁶. 5 The colony count was determined by incubating the agar plates at 37°C for 12 h. The agar plates were then incubated again before counting to determine the final colony count. Bacterial viability was calculated as the ratio of the number of colonies in the treatment group to the number of colonies in the control group (n = 3 independent replicates). Data are presented as mean ± SD, *p < 0.05, ***p < 0.001; one-way ANOVA with multiple comparison tests were performed, all tests were two-tailed. (c) Comparison with reported effective antibacterial concentrations in the literature. (d) Photographs of bacterial protein exudation (n = 3 biologically independent replicates). (e) Statistical analysis of colony formation on MRSA agar plates. (h) Comparison of antibacterial effects on agar plates (n = 3 biologically independent replicates): p < 0.001 compared to the PBS / H2O2 / Pt group; p = 0.1059 compared to the PBS group. Crystal violet staining showed biofilm inhibition (f) and disruption (g). Results of biofilm bacterial abundance determination for different sample treatments (i) (n=3 biologically independent replicates): p-value < 0.001 compared with PBS / H2O2 / Pt group; p-value = 0.0144 compared with PBS group.
[0045] Figure 6The in vitro reactive oxygen species scavenging and cell protection effects of PtFeCuCoNi were demonstrated. (a) Quantitative analysis of DCFH-DA fluorescence in various cells under different treatment conditions; Left panel: Compared with the H2O2 / Pt group, the PtFeCuCoNi group p < 0.001; compared with the control group, p(hydrogen peroxide) < 0.001, p(PtFeCuCoNi) = 0.0886; Middle panel: Compared with the H2O2 / Pt group, the PtFeCuCoNi group p < 0.001; compared with the control group, p(hydrogen peroxide) < 0.001, p(PtFeCuCoNi) = 0.0545; Right panel: Compared with the hydrogen peroxide group, the PtFeCuCoNi group p < 0.001; compared with the Pt group, the PtFeCuCoNi group p < 0.001; compared with the control group, p(hydrogen peroxide) < 0.001, p(PtFeCuCoNi) = 0.3634; compared with the Pt group, the PtFeCuCoNi group p=0.0095; (b) Quantitative analysis of cell viability under different treatment conditions; Left figure: compared with the hydrogen peroxide / Pt nanoparticle group, p(PtFeCuCoNi) < 0.001; p(PtFeCuCoNi) = 0.0505, p(hydrogen peroxide) < 0.001, compared with the control group (n = 4 independent replicates); Middle figure: compared with the hydrogen peroxide / Pt nanoparticle group, p(PtFeCuCoNi) < 0.001; p(PtFeCuCoNi) = 0.5933, p(hydrogen peroxide) < 0.001, compared with the control group (n = 4 independent replicates); Right figure: compared with the hydrogen peroxide / Pt nanoparticle group, p(PtFeCuCoNi) < 0.001; p(PtFeCuCoNi) = 0.3177, p(hydrogen peroxide) <0.001, compared with the control group (n = 6 independent replicates); (c) Linear distribution of fluorescence intensity of cytoskeleton staining; (d) Quantitative analysis of cell area (n = 12 independent replicates); compared with the Pt group, p(PtFeCuCoNi) = 0.01; compared with the hydrogen peroxide group, p(PtFeCuCoNi) = 0.002; compared with the control group, p(PtFeCuCoNi) = 0.5358; compared with the control group, p(hydrogen peroxide) <0.001; (e) Quantitative analysis of the main segment of angiogenesis experiment of human umbilical vein endothelial cells (HUVEC) after different interventions (n = 3 independent biological replicates); compared with the Pt group, p(PtFeCuCoNi) = 0.003; compared with the hydrogen peroxide group, p(PtFeCuCoNi) = 0.0002; compared with the control group, p(PtFeCuCoNi) = 0.044; p(hydrogen peroxide) <0.001 compared with the control group; Raw264 after 24 hours of LPS stimulation.Relative quantitative analysis of CCR7(f) and CD163(g) in cells relative to the control group: (f): p(PtFeCuCoNi) < 0.001 compared to the LPS / Pt NPs group; p(PtFeCuCoNi) = 0.0752 compared to the control group; p(hydrogen peroxide) < 0.001 compared to the control group (n = 5 independent replicates); (g): p(PtFeCuCoNi) < 0.001 compared to the control / LPS / Pt NPs group; p(Pt) = 0.0365 compared to the control group; p(LPS) = 0.556 compared to the control group (n = 5 independent replicates). Control group: untreated cells; LPS: cells treated with LPS; Pt NPs and PtFeCuCoNi HEA NPs: cells pretreated with the corresponding ROS scavengers and then co-incubated with LPS. Detailed Implementation
[0046] Inspired by peroxisome oxidative signaling, this invention develops a pH-adaptive high-entropy alloy (HEA) nanoparticle, PtFeCuCoNi. This nanomaterial stabilizes the d-band center through a multi-metal "cocktail effect," optimizing oxygen species binding capacity and seamlessly switching between different enzyme-mimicking activities. In an acidic microenvironment, these nanoenzymes, acting as potent oxidases, generate reactive oxygen species (ROS), effectively killing methicillin-resistant Staphylococcus aureus (MRSA), a typical multidrug-resistant pathogen, and disrupting biofilms at an ultra-low minimum inhibitory concentration (MIC) of 8 μg / mL, far lower than values reported in similar systems. Under physiological pH (7.4), they transform into superoxide dismutase and catalase-like functions, efficiently scavenging intracellular ROS, alleviating oxidative stress, while maintaining the survival and proliferation of endothelial cells, fibroblasts, and macrophages, with extremely low cytotoxicity. In a wound model of MRSA infection, the PtFeCuCoNi HEA nanoparticles accelerated bacterial clearance and promoted tissue repair. By enhancing angiogenesis and extracellular matrix remodeling, this material ultimately achieves faster wound healing. Mechanistic studies have shown that it can activate the Nrf2 antioxidant pathway, inhibit the secretion of pro-inflammatory cytokines, and promote macrophage polarization towards the reparative M2 phenotype, thereby constructing an immune regeneration microenvironment. Therefore, by combining potent acid-activated antibacterial activity with effective neutral pH immunomodulation on a single ultra-low dose platform, this pH-adaptive nanozyme addresses the dual challenges of drug resistance and chronic inflammation, providing a multifunctional strategy for combating persistent infection and promoting tissue regeneration.
[0047] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.
[0048] Materials and reagents: Iron acetylacetone (Fe(acac)2), copper nitrate hydrate (Cu(NO3)2·3H2O), cobalt nitrate hexahydrate (Co(NO3)2·6H2O), nickel nitrate hexahydrate (Ni(NO3)2·6H2O), N,N-dimethylformamide (DMF), ethylene glycol (EG), hydrogen peroxide (H2O2), 3,3',5,5'-tetramethylbenzidine (TMB), 5,5-dimethyl-1-pyrrolidone N-oxide (DMPO), 2,2,6,6-tetramethylpiperidine (TEMP), tert-butanol (TBA), benzoquinone (BQ), sodium azide (NaN3), potassium superoxide (KO2), nitrotetrazole blue chloride (NBT), and 9,10-dibenzoanthraquinone (DPA) were all purchased from Aladdin Reagent Company (Shanghai, China). Platinum bis(acetylacetone) (Pt(acac)2) was purchased from Anhui Nengke Chemical Reagent Co., Ltd. Titanium sulfate (Ti(SO)4) was purchased from Mackintosh Reagents, Inc. (Shanghai, China).
[0049] Example: Preparation of PtFeCuCoNi high-entropy alloy nanoparticles
[0050] The synthesis process and structure of PtFeCuCoNi high-entropy alloy nanoparticles are shown in the figure below. Figure 1 As shown in a. This invention uses palladium acetylacetonate, iron acetylacetonate, copper nitrate trihydrate, cobalt nitrate hexahydrate, and nickel nitrate hexahydrate as metal precursors, and N,N-dimethylformamide (DMF) and ethylene glycol (EG) as solvents. An orange, finely dispersed raw material mixture is formed through ultrasonic treatment. As the temperature increases, the mixture gradually turns black, which may be due to the coordination reaction and co-reduction of the five metals. Subsequently, a single-phase high-entropy alloy is successfully formed.
[0051] Specifically, Pt(acac)₂ (20 mg), Fe(acac)₂ (17.96 mg), Cu(NO₃)₂·3H₂O (12.1 mg), Co(NO₃)₂·6H₂O (17.65 mg), and Ni(NO₃)₂·6H₂O (17.63 mg) were placed in a 100 mL polytetrafluoroethylene-lined autoclave, and a mixed solution of DMF (12 mL) and ethylene glycol (8 mL) was added. The mixture was sonicated for 30 minutes to completely dissolve all reactants. The resulting solution was heated at 200 °C for 8 hours. The final product was washed with ethanol and acetone and collected by centrifugation at 10,000 rpm.
[0052] Comparative example:
[0053] Using the same method as in the examples, single Pt particles were prepared as a control using Pt(acac)2 as the raw material via a solvothermal method.
[0054] Quaternary metal high-entropy alloy nanoparticles lacking Pt, Fe, Cu, Co, or Ni were also prepared using the same method as in the examples.
[0055] Test Example 1: Structural Characterization of PtFeCuCoNi High-Entropy Alloy Nanoparticles
[0056] To observe the morphology and size of high-entropy alloy nanoparticles (HEA NPs), we characterized the prepared products using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and high-resolution transmission electron microscopy (HRTEM). The SEM and TEM characterization results are shown below. Figure 1 As shown in bd, it shows that HEA nanoparticles are uniformly distributed in small spherical shapes. HRTEM images further reveal that the PtFeCuCoNi high-entropy alloy nanoparticles have high crystallinity, and the clear lattice fringes of their (111) crystal plane can be verified by the corresponding fast Fourier transform (FFT) spectrum. Figure 1 e). Furthermore, the inverse FFT spectra and their corresponding integrated pixel intensities show that the average lattice spacing fluctuates between 0.212 nm and 0.215 nm. Figure 1 f) indicates that the PtFeCuCoNi high-entropy alloy nanoparticles exhibit significant lattice distortion and approximately 3.3% intrinsic tensile strain, which stems from factors such as differences in atomic size among components, indentation defects, and ultrathin thickness. Low-magnification, high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) energy-dispersive X-ray spectroscopy (EDS) images show that platinum, iron, copper, cobalt, and nickel elements exhibit a uniform distribution. Figure 1 g).
[0057] The crystal structures of PtFeCuCoNi high-entropy alloy nanoparticles and materials prepared in comparison were characterized by powder X-ray diffraction (XRD). The XRD patterns revealed a typical platinum face-centered cubic structure with no obvious phase separation. With the formation of PtFeCuCoNi high-entropy alloy nanoparticles, the characteristic peak shifted to a higher angle, indicating that more atoms were successfully alloyed with the platinum nanoparticles to successfully prepare the high-entropy alloy. Figure 2 a). Simultaneously, the atomic ratios of Pt / Fe / Cu / Co / Ni in the PtFeCuCoNi high-entropy alloy nanoparticles were determined by inductively coupled plasma mass spectrometry (ICP-MS) to be 19.1 / 14.7 / 20.9 / 22.3 / 23.0 (a). Figure 2 b). X-ray photoelectron spectroscopy (XPS) was used as a surface-sensitive probe to conduct an in-depth analysis of the chemical state and composition of the surface of PtFeCuCoNi high-entropy alloy nanoparticles. For example... Figure 2As shown in the cg, experimental data confirm that this material contains platinum (Pt), iron (Fe), copper (Cu), cobalt (Co), and nickel (Ni). Specifically: platinum's 4f 7 / 2 and 4f 5 / 2 Characteristic peaks are located at 71.22 and 74.54 electron volts, respectively; the 2p group of iron... 3 / 2 and 2p 1 / 2 Characteristic peaks are located at 714.12 and 723.69 electron volts, respectively; the 2p peaks of copper... 3 / 2 and 2p 1 / 2 Characteristic peaks are located at 931.85 and 951.62 electron volts, respectively; the 2p peaks of cobalt are... 3 / 2 and 2p 1 / 2 Characteristic peaks are located at 778.14 and 792.83 eV, respectively; nickel's 2p... 3 / 2 and 2p 1 / 2 Characteristic peaks are located at 852.41 and 869.69 electron volts. Binding energy analysis shows that platinum, iron, copper, cobalt, and nickel exist in alloy form within the PtFeCuCoNi high-entropy alloy nanoparticles.
[0058] X-ray absorption near-edge structure (XANES) spectroscopy shows that the intensity of the "white line" (WL) on the L3 edge of platinum metal is completely consistent with that of the platinum foil and is significantly lower than that of PtO2, indicating that electrons are enriched on the platinum atoms. Figure 2 h). The high-entropy alloy (HEA) shows a peak at approximately 2.3 Å in the Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum in R space, corresponding to platinum-platinum interactions. This shifted peak indicates the presence of platinum-metal (M = Fe, Cu, Ni, Co) interactions within the alloy, which may be due to the synergistic effect of multiple elements in the alloy. Figure 2 i). No characteristic peaks of Pt-O bonds were detected in the FT-EXAFS spectrum of the high-entropy alloy, strongly indicating that the sample did not undergo oxidation, thus preserving its metallic properties. Furthermore, wavelet transform (WT) can further distinguish between Pt-O and Pt-Pt bonds oscillating on the L3 edge of platinum. Figure 2 j). Platinum foil in R space R = 2.7 Å and k space k = 10.8 Å. -1 The Pt-Pt bond spectrum is clearly displayed at the PtO2 value, and the R-space spectrum (R = 3.0 Å) and the k-space spectrum (k = 11.0 Å) are also observed. -1 The Pt-Pt bond spectrum at 7.8 Å was observed in the wavelet profile of the PtFeCuCoNi high-entropy alloy nanoparticles, consistent with the EXAFS spectral results. This finding supports the theoretical view that intermetallic coordination bonds exist within the platinum-metal matrix.
[0059] The testing equipment and parameters used in this test case are as follows: Scanning electron microscope (SEM) images were captured using the Apreo S HiVoc system manufactured by Thermo Fisher Scientific. Transmission electron microscope (TEM) images and energy dispersive spectroscopy (EDS) spectra were acquired using a Talos F200x TEM from FEI Corporation at an accelerating voltage of 200 kV. Distortion-corrected scanning transmission electron microscopy (AC-STEM) characterization was performed using a FEI Titan Cubed Themis G2 300 system for magnified high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). Crystal phase states were determined using a DX-2700BH X-ray diffractometer (with a copper target, operating voltage of 40 kV). X-ray photoelectron spectroscopy (XPS) measurements were performed using a Thermo Fisher Scientific K-Alpha™+ X-ray photoelectron spectrometer equipped with a hemispherical 180° bifocal analyzer and a 128-channel detector. Electron paramagnetic resonance (EPR) measurements were performed using a Bruker EMRXPlus spectrometer (Bruker Beijing Technology Co., Ltd., USA), operating at 9.8 GHz (microwave power 1 mW). Raman spectroscopy was performed using a Hochigami HR Evolution Raman spectrometer (532 nm laser source). X-ray absorption spectroscopy (XAS) was acquired at the BL07A1 beamline of the National Synchrotron Radiation Research Center and monochromated using a silicon (111) double crystal monochromator. Processing and analysis of XANES (X-ray near-edge structure) and EXAFS (Extended X-ray Absorption Fine Structure) data were performed using Athena software.
[0060] Test Example 2: pH-Adaptive Reactive Oxygen Catalytic Activity Test of PtFeCuCoNi High-Entropy Alloy Nanoparticles
[0061] After determining the chemical and electronic structures of the PtFeCuCoNi high-entropy alloy nanoparticles, we investigated their enzyme-like activities, particularly their pH-adaptive biocatalytic capabilities designed for bacterial-infected diabetic ulcers. In short, under acidic conditions, the PtFeCuCoNi high-entropy alloy nanoparticles mimic peroxidase (POD) to convert harmless hydrogen peroxide into highly toxic reactive oxygen species (•O2- and...). 1 O2, thus exerting a bactericidal effect; in a neutral environment, the nanoparticles can mimic the function of superoxide dismutase (SOD), converting •O2- into hydrogen peroxide and using catalase (CAT)-like activity to decompose excess hydrogen peroxide into non-cytotoxic O2 and water to alleviate intracellular oxidative stress, thereby promoting cell proliferation. Figure 3 a).
[0062] To verify the catalytic performance of PtFeCuCoNi high-entropy alloy nanoparticles, we first evaluated their reactive oxygen species (ROS) generation capacity in an acidic environment using a 3,3,5,5-tetramethylbenzidine (TMB) colorimetric method. This colorimetric agent oxidizes to form a blue product, oxTMB, with a characteristic absorption peak at 652 nm. Figure 3 b and Figure 3 As shown in Figure c, the PtFeCuCoNi high-entropy alloy nanoparticles exhibited the best reactive oxygen species (ROS) generation performance, with the strongest luminescence intensity at 652 nm, and displayed pH-adaptive catalytic activity—producing almost no ROS under neutral conditions. To further explore the synergistic effect of the PtFeCuCoNi catalyst and clarify the role of each element in the POD-like biocatalyst, we synthesized a series of quaternary nanocatalysts with similar loadings by sequentially removing elements (i.e., FeCuCoNi, PtCuCoNi, PtFeCoNi, PtFeCuNi, and PtFeCuCo). The reaction rate decreased sequentially with the removal of Fe, Pt, Cu, Co, and Ni: the largest decrease was observed with the removal of Fe, and the smallest decrease with the removal of Ni. Notably, the reaction rates of these quaternary catalysts were all lower than those of PtFeCuCoNi, indicating that the five elements synergistically regulate the reaction kinetics of ROS generation. Figure 3 d).
[0063] To quantify the efficiency of PtFeCuCoNi high-entropy alloy nanoparticles (HEA) in catalyzing the generation of reactive oxygen species (ROS), we systematically analyzed its characteristic steady-state kinetic parameters, including the catalytic constant (Km / mM), maximum reaction rate (Vmax / μM s⁻¹), and turnover rate (TON / s). Figure 4 As shown in figure a, PtFeCuCoNi HEA nanoparticles (Vmax = 10.23, TON = 0.208) exhibit superior peroxidase (POD) catalytic kinetics compared to platinum-based materials (Vmax = 7.67, TON = 0.03), fully demonstrating that the high-entropy effect significantly enhances the catalytic performance of this material. Furthermore, its enzymatic indices are comparable to mainstream POD-based biocatalysts, and even surpass most recently reported metal oxide and metal nanoparticle-based enzyme mimics (see Figure a). Figure 4 b). Through free radical quenching experiments, we successfully identified the types of ROS generated by PtFeCuCoNi HEA nanoparticles, namely ·O2- and ·O2-. 1 O2 ( Figure 4 c). Electron paramagnetic resonance (EPR) detection further confirmed that the main ROS in this material are ·O2- and ·O2- when 5,5-dimethyl-1-pyrrolline N-oxide (DMPO) and 2,2,6,6-tetramethylpiperidine (TEMP) are used as specific spin-trapping reagents. 1O2 ( Figure 4 d). In summary, the above results show that PtFeCuCoNi materials exhibit excellent reactive oxygen generation performance.
[0064] Given that residual reactive oxygen species (ROS) after bacterial removal may trigger cellular oxidative stress, thereby affecting cell viability and function and hindering wound healing, we subsequently investigated the ROS scavenging ability of PtFeCuCoNi high-entropy alloy nanoparticles (HEANPs) under neutral conditions. First, their •O2- scavenging performance was evaluated using the nitrotetrazole blue-chloride (NBT) colorimetric method. The results showed that the absorbance of PtFeCuCoNi HEA NPs at 680 nm was significantly lower than that of platinum nanoparticles (Pt NPs), indicating superior •O2- scavenging efficiency—achieving a scavenging rate of 90.42% within 5 minutes, significantly better than platinum nanoparticles (73.48%). Figure 4 e).
[0065] Besides the aforementioned free radicals, hydrogen peroxide is another important reactive oxygen species that triggers intracellular oxidative stress. Therefore, we further investigated the ability of PtFeCuCoNi high-entropy alloy (HEA) and platinum nanoparticles to scavenge hydrogen peroxide, and their catalase-like activity in decomposing hydrogen peroxide into non-toxic substances water and O2. Time-adaptive hydrogen peroxide scavenging experiments showed that PtFeCuCoNi HEA nanoparticles significantly outperformed platinum nanoparticles, achieving a hydrogen peroxide scavenging rate of up to 85% within 30 minutes, indicating that they almost completely neutralized hydrogen peroxide. Figure 4 f). The concurrent O2 generation experiment is consistent with the results of hydrogen peroxide decomposition ( Figure 4 (g) This confirms that PtFeCuCoNi HEA nanoparticles can rapidly and efficiently decompose hydrogen peroxide into O2 and water. Furthermore, we evaluated the binding affinity of PtFeCuCoNi HEA nanoparticles to hydrogen peroxide and the reaction rate by calculating Vmax, Km, and TON values. Figure 4 As shown in h, the Vmax value of platinum nanoparticles is 51.53 μM s⁻¹, while after introducing multiple elements to form a high-entropy alloy, the Vmax value of PtFeCuCoNi HEA nanoparticles increases to 82.14 μM s⁻¹, an increase of 1.6 times. The calculated TON value is 7.58 s⁻¹, a value that is particularly outstanding among current reactive oxygen species scavenging materials based on metal compounds. Figure 4 i). These indicators fully demonstrate that PtFeCuCoNi HEA nanoparticles have the ability to rapidly capture hydrogen peroxide, highlighting their excellent reaction kinetics.
[0066] Notably, the PtFeCuCoNi high-entropy alloy nanoparticles exhibit pH-adaptive reactive oxygen species (ROS) generation and scavenging characteristics: ROS generation is significantly enhanced in acidic environments, while scavenging is dominant under neutral conditions, fully validating their excellent microenvironment adaptability. The comprehensive research results demonstrate that by introducing multiple elements to construct a high-entropy alloy modification strategy, a dynamic pH-adaptive treatment protocol can be achieved—accelerating ROS generation in acidic environments and efficiently scavenging reactive oxygen species under neutral conditions, thereby effectively combating bacterial infections and promoting wound healing.
[0067] Test Example 3: PtFeCuCoNi high-entropy alloy nanoparticles eliminate MRSA under acidic conditions via ROS.
[0068] After confirming the potent ability of PtFeCuCoNi alloy to promote the generation of reactive oxygen species (ROS) under acidic conditions, we systematically evaluated its antibacterial properties against methicillin-resistant Staphylococcus aureus (MRSA). MRSA, a common and widely drug-resistant pathogen in clinical practice, frequently causes skin and soft tissue infections. Experimental data showed that in an acidic environment, the ROS generated by the synergistic effect of PtFeCuCoNi and hydrogen peroxide mainly consists of ·O₂⁻ and singlet oxygen (…). 1 O2), while no peroxidase-like (POD) activity was observed in a neutral environment. OD and plate assays showed that the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the PtFeCuCoNi alloy were only 8 μg / mL ( Figure 5 a and 5b), their doses were significantly lower than the typical doses reported in the literature for similar nanozyme-based antibacterial systems (a and 5b). Figure 5 c).
[0069] To evaluate the bactericidal effect of the alloy on planktonic bacteria, we quantified the amount of cytoplasmic contents released using a protein leakage experiment. The PtFeCuCoNi treatment group showed significantly increased membrane permeability and cytoplasmic leakage, indicating that the integrity of the bacterial envelope was severely disrupted. Figure 5 d). Colony forming unit (CFU) analysis consistently showed that MRSA was almost completely eliminated in samples treated with a combination of PtFeCuCoNi and hydrogen peroxide, while no significant bactericidal effect was observed with hydrogen peroxide alone. The antibacterial efficacy of this alloy is significantly superior to that of platinum alone, reducing the number of viable bacteria by only 21.49% under the same oxidizing conditions. Figure 5 (e, h) This indicates that PtFeCuCoNi nanozymes exhibit a significant synergistic antibacterial effect under oxidative conditions. Notably, these findings collectively demonstrate that PtFeCuCoNi can exert potent bactericidal activity against drug-resistant pathogens even at very low doses under physiologically challenging microenvironmental conditions.
[0070] Based on the observed reactive oxygen species-mediated lipid peroxidation in the biofilm matrix, we further evaluated the overall anti-biofilm effect of the alloy. Quantitative crystal violet staining results showed that the total biofilm biomass decreased by approximately 90% after PtFeCuCoNi treatment, confirming that the alloy possesses a strong biofilm scavenging ability. Figure 5 f, g, i).
[0071] Test Example 4: Reactive Oxygen Scavenging and Cell Protection Effects of PtFeCuCoNi High-Entropy Alloy Nanoparticles at Neutral pH
[0072] Based on its proven antioxidant enzyme-like activity, we further evaluated the ability of PtFeCuCoNi high-entropy alloy nanoparticles to scavenge oxidative stress and restore cellular homeostasis under physiological pH conditions (pH 7.4). Preliminary cell compatibility experiments showed that at a concentration of 4 μg mL⁻¹, the material had no significant toxicity to human umbilical vein endothelial cells (HUVECs), mouse renal cardiomyocytes (RSFs), and RAW264.7 macrophages; therefore, all subsequent experiments used a concentration of 2 μg mL⁻¹. Quantitative fluorescence analysis after 2,7-dichlorofluorescein diacetate (DCFH-DA) staining revealed that intracellular reactive oxygen species (ROS) levels significantly increased after hydrogen peroxide treatment, but cell viability essentially returned to baseline levels after treatment. Figure 6 a). The protective ability of HEA nanoparticles in a reactive oxygen species environment was evaluated using representative live / dead cell double staining fluorescence images. Quantitative results of live / dead cell staining showed that, unlike the untreated group or the platinum-only control group which exhibited extensive cell death, PtFeCuCoNi effectively inhibited H2O2-induced cell death (a). Figure 6 b).
[0073] To verify whether this cytoprotective effect translates into structural toughness, we examined the distribution of F-actin in human umbilical vein endothelial cells (HUVECs) and mouse renal cardiomyocytes (RSFs). Phalloidin staining showed that hydrogen peroxide exposure led to significant depolymerization of F-actin, while PtFeCuCoNi maintained the integrity of the cytoskeleton, with its cell area being no different from the unexposed control group. Figure 6 c, d). Tube formation experiments showed that HUVECs treated with PtFeCuCoNi formed more branching points and extended into capillary-like networks than cells exposed to hydrogen peroxide alone. Figure 6 e), which indicates that maintaining the cytoskeleton is fundamental to enhancing migration and angiogenesis.
[0074] Besides its cytoprotective effects, effectively clearing the pro-inflammatory microenvironment is crucial for recovery after bacterial infection, a process primarily regulated by macrophage plasticity. To verify this, we investigated the immunomodulatory effects of PtFeCuCoNi on macrophage polarization in LPS-stimulated RAW264.7 cells. Notably, pretreatment with PtFeCuCoNi significantly downregulated CCR7 expression—a hallmark marker of pro-inflammatory M1 macrophages—compared to LPS or Pt treatment alone. Figure 6 f). Meanwhile, the enhanced expression of CD163 induced by PtFeCuCoNi was significantly greater than that in the control group, confirming that it could significantly promote the transformation of macrophages to the reparative M2 phenotype. Figure 6 g). These results combined indicate that PtFeCuCoNi can effectively reprogram macrophages from an inflammatory state to a repair state by scavenging reactive oxygen species and exerting cytoprotective effects, thereby creating an immune regeneration environment conducive to healing.
[0075] Summary and discussion:
[0076] In summary, inspired by the innate immune-redox regeneration (IADS) mechanism in the human body, this invention innovatively synthesizes PtFeCuCoNi high-entropy alloy (HEA) nanoparticles using a one-step solvothermal method. These HEA nanoparticles mimic the dynamic enzymatic behavior of natural peroxisomes, exhibiting superior reactive oxygen species regulation characteristics in complex wound environments, and are able to coordinate antibacterial activity and tissue repair function.
[0077] Mechanistic studies have shown that the synergistic effect of multiple metal active sites—especially the synergistic effect between cobalt (Co) and iron (Fe) atoms—endows high-entropy alloy nanoparticles (HEA NPs) with pH-responsive enzyme-mimicking activity. Specifically, cobalt promotes hydrogen peroxide adsorption, while ruthenium regulates the binding of oxygen intermediates. The combined effect of these two factors significantly enhances the catalytic efficiency of reactive oxygen species (ROS), far exceeding the level of traditional platinum-based nanoparticles.
[0078] Notably, HEA nanoparticles not only exhibit excellent catalytic performance but also demonstrate significant biological functions in an MRSA-infected wound model. During the acidic infection phase, they effectively generate reactive oxygen species (ROS), achieving bacterial clearance and biofilm disruption. During the neutral repair phase, they alleviate oxidative stress-induced DNA damage and apoptosis in endothelial and fibroblast cells by scavenging excess ROS, thereby promoting angiogenesis (CD31 / VEGF) and the deposition of collagen-rich extracellular matrix. Transcriptome analysis further confirmed the activation of antioxidant pathways (such as Nrf2 and SLC7A11) and the inhibition of pro-inflammatory genes (such as CHAC1 and SESN2), which helps maintain immune homeostasis and accelerate wound healing. In vitro experiments showed that HEA nanoparticles can enhance fibroblast migration, promote tubular structure formation in human umbilical vein endothelial cells (HUVECs), and induce M2-like macrophage polarization (upregulation of CD206 and Arg1 expression), indicating their stage-specific wound repair capabilities adapted to the microenvironment.
[0079] Comprehensive research results indicate that PtFeCuCoNi high-entropy alloy nanoparticles (HEA) demonstrate broad application prospects as a novel multifunctional biocatalyst. Their powerful reactive oxygen species regulation capabilities not only make them ideal for combating drug-resistant infections and promoting tissue regeneration, but also offer wide applicability in redox-related biomedical fields such as chronic inflammation, diabetic wound repair, ischemic disease treatment, and tumor microenvironment remodeling.
[0080] It should be noted that while the preferred embodiments of the present invention are given in the specification and accompanying drawings, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. These embodiments are not intended to impose additional limitations on the content of the present invention; their purpose is to provide a more thorough and comprehensive understanding of the disclosure of the present invention. Furthermore, the above-described technical features can be combined with each other to form various embodiments not listed above, all of which are considered to be within the scope of the present invention specification. Moreover, those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. An application of high-entropy alloy nanoparticles as a biocatalyst, characterized in that, The high-entropy alloy nanoparticles are composed of Pt, Fe, Cu, Co and Ni; The high-entropy alloy nanoparticles have the ability to promote the generation and removal of reactive oxygen species with pH adaptability. This application is not intended for diagnosis or treatment.
2. The application according to claim 1, characterized in that, The high-entropy alloy nanoparticles have the ability to promote the generation of reactive oxygen species under acidic conditions and the ability to promote the scavenging of reactive oxygen species under neutral conditions.
3. The application according to claim 1, characterized in that, The high-entropy alloy nanoparticles have pH-adaptive POD-like, SOD-like, and / or CAT-like enzyme activities.
4. The application according to claim 3, characterized in that, The high-entropy alloy nanoparticles exhibit POD-like enzyme activity under acidic conditions and SOD-like and / or CAT-like enzyme activity under neutral conditions.
5. The application according to claim 1, characterized in that, The atomic proportions of Pt, Fe, Cu, Co, and Ni in the high-entropy alloy nanoparticles are 5% to 35%.
6. The application according to claim 5, characterized in that, The atomic ratio of Pt, Fe, Cu, Co and Ni in the high-entropy alloy nanoparticles is 19.1:14.7:20.9:22.3:23.
0.
7. The use of high-entropy alloy nanoparticles as defined in any one of claims 1-6 in the preparation of materials for scavenging bacteria and disrupting biofilms under acidic conditions and / or scavenging reactive oxygen species under neutral conditions, protecting cells to alleviate damage caused by oxidative stress, and anti-inflammatory effects.
8. The application according to claim 7, characterized in that, The bacteria in question are drug-resistant bacteria.
9. The application according to claim 8, characterized in that, The bacteria in question are methicillin-resistant Staphylococcus aureus; The minimum inhibitory concentration of the high-entropy alloy nanoparticles is 8 μg / mL.
10. The use of high-entropy alloy nanoparticles as defined in any one of claims 1-6 in the preparation of products for treating wound infections and accelerating wound healing.
Citation Information
Patent Citations
Efficient antibacterial high-entropy alloy nanoparticles as well as preparation method and application thereof
CN115958192A
Application of doping-based multi-enzyme active nano material in treatment of inflammatory diseases
CN117731693A
Application of high-entropy alloy nano-enzyme in antibiotic degradation and antibiosis
CN119954289A
High-entropy alloy nanoparticle and application thereof
CN120000686A
Multi-enzyme activity high-entropy alloy material as well as preparation method and application thereof
CN120624911A
Cited By
Application of non-ROS dependent luminous energy enzyme in photocatalysis and Nrf2 activation
CN121244291A
High-entropy nano-enzyme hydrogel for treating scalds as well as preparation method and application of high-entropy nano-enzyme hydrogel
CN122031517A